Validation of Lathyrus egirdiricus and three new combinations in Leobordea and Senegalia (Leguminosae) - Silva, Lucas Almeida; Freitas, Joelcio; Dutra, Valquíria Ferreira; Alves-Araújo, Anderson (Phytotaxa, 2014)
The family Leguminosae Jussieu comprises about 730 genera and 19.400 species divided in three subfamilies: Mimosoideae, Papilionideae and Caesalpinioideae (Lewis et al. 2005), bearing a huge diversity of habits from small annual herbs to large trees. They can be found in all terrestrial habitats, from rainforests to deserts (Polhill et al., 1981; Lewis et al. 2005).